2021
DOI: 10.1177/13567667211053387
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking and tourism research: A systematic literature review

Abstract: In recent years, the number of studies in tourism using the eye tracking technique has increased and started generating valuable information for both academics and the industry. However, there is a gap in the literature concerning systematic reviews focused on recent articles and their findings. Thus, the aim of this study is to close this gap by systematically analysing 70 research papers tackling the subject of eye tracking in tourism and published in highly ranked tourism journals. The study identifies the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…For systematic reviews , Scott et al [ 13 ], Atabay and Güzeller [ 14 ], and Savin et al [ 8 ] assessed the application of ET in tourism research. Meanwhile, Li et al [ 15 ] investigated the use of EEG in tourism and hospitality studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For systematic reviews , Scott et al [ 13 ], Atabay and Güzeller [ 14 ], and Savin et al [ 8 ] assessed the application of ET in tourism research. Meanwhile, Li et al [ 15 ] investigated the use of EEG in tourism and hospitality studies.…”
Section: Resultsmentioning
confidence: 99%
“…Each neuromarketing technique gathers different neural activity measurements. For example, fMRI assesses metabolic brain processes through variations in blood flow, while EEG records electrical changes in brain signals on the scalp [ 7 ]; ET measures eye attention toward a stimulus [ 8 ]; galvanic skin response gauges electrodermal activities through sweat production [ 9 ]; FAC measures feelings as expressions appear on the face; and HT counts the number of heartbeats in a time and can be used to determine stress [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The final round aimed to 100% consensus, striving to resolve all discrepancies through comprehensive discussions. As previous research (Cruz-Suárez et al, 2020; Díez-Martín et al, 2023; Savin et al, 2022), we have analysed the common links between the papers of each cluster to distil their key aspects and enhance the robustness of the cluster labelling process. This procedure made it possible to summarise the essence of each research cluster.…”
Section: Methodsmentioning
confidence: 99%
“…Tourists’ perception of the tourism website is related to its visual appearance (Savin et al, 2022); the layout, pictures, and overall design of a website or app are all examples (Perez-Vega et al, 2018). Wobbrock et al (2021) demonstrated that visual appearance can affect online news credibility judgments.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%